Advances in Methods for Recovery of Ferrous, Alumina, and Silica Nanoparticles from Fly Ash Waste - Virendra Kumar Yadav; Madhusudan Hiraman Fulekar (Ceramics, 2020)
Fly ash or coal fly ash causes major global pollution in the form of solid waste and is classified as a “hazardous waste”, which is a by-product of thermal power plants produced during electricity production. Si, Al, Fe Ca, and Mg alone form more than 85% of the chemical compounds and glasses of most fly ashes. Fly ash has a chemical composition of 70–90%, as well as glasses of ferrous, alumina, silica, and CaO. Therefore, fly ash could act as a reliable and alternative source for ferrous, alumina, and silica. The ferrous fractions can be recovered by a simple magnetic separation method, while alumina and silica can be extracted by chemical or biological approaches. Alumina extraction is possible using both alkali- and acid-based methods, while silica is extracted by strong alkali, such as NaOH. Chemical extraction has a higher yield than the biological approaches, but the bio-based approaches are more environmentally friendly. Fly ash can also be used for the synthesis of zeolites by NaOH treatment of variable types, as fly ash is rich in alumino-silicates. The present review work deals with the recent advances in the field of the recovery and synthesis of ferrous, alumina, and silica micro and nanoparticles from fly ash.